THE NEXUS BETWEEN INFLATION, TRADE, AND FDI WITH ECONOMIC SUSTAINABILITY IN MALAYSIA - Faridah Pardi; Mohd Azlan Abd Majid; Sutina Junos (Journal of Academia, 2021)
The Adjusted Net Saving (ANS) rate indicator was introduced by the World Bank in the early 1990s to measure the sustainable development path of a country. Since then, the indicator has been widely recognized for its comprehensive economic sustainability measurement. This paper explored the nexus between inflation rate, international trade and foreign direct investment (FDI) with the economic sustainability path in Malaysia from 1990 to 2018. We employed the autoregressive distributed lag (ARDL) model based on the Bounds test approach to identify the connection among the listed variables. The result findings showed that in the long run, trade and FDI have a significant positive impact on the ANS rate while the inflation rate, however, presented otherwise. Following the cointegrating short-run model, the error correction term indicates a highly significant negative form which confirms the correct speed of adjustment towards the equilibrium. As the Coronavirus pandemic is currently affecting the global economy, this study further recommends that investment and international trade policies must be meticulously be reformulated to ensure sustained development in an emerging economy like Malaysia.